Effects of branched chain amino acids on sow and litter performance - S A Moser; J A Loughmiller; Michael D Tokach; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1998)
Three hundred-six sows were used to evaluate effects of the interrelationship among valine, isoleucine, and leucine on sow and litter performance. Eight dietary treatments were arranged as a 2x2x2 factorial with two levels of valine (.80 and 1.20%), isoleucine (.68 and 1.08%), and leucine (1.57 and 1.97%). Litter weaning weight, litter weight gain from d 2 to weaning, and sow backfat loss increased as dietary valine increased but were not affected by dietary isoleucine or leucine. Increasing dietary valine, isoleucine, or leucine did not affect milk fat, DM, CP, or lactose. These results confirm the importance of dietary valine for increased litter weaning weight, independent of either additional dietary isoleucine or leucine.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Valine; Isoleucine; Leucine